THE EFFECT OF DIABETES SELF-MANAGEMENT EDUCATION (DSME) PROGRAM ON QUALITY OF LIFE IN DIABETES MELLITUS PATIENTS - Handayani, Tut; Nusdin, Nusdin (Universitas Islam Negeri Alauddin Makassar, 2021)
In people with diabetes mellitus, changes in the quality of life and risk of death can be experienced due to complications, this is because diabetes mellitus cannot be cured, allowing complications of other diseases that can worsen health conditions, but not all sufferers can experience it if they can maintain or control their condition so that can live healthier. To reduce this, a diabetes mellitus management program is needed where there is a regulation of diet, activity, blood sugar control and exercise through a program called Diabetes Self-Management Education (DSME). The purpose of this study was to analyze the effect of Diabetes Self-Management Education and Support (DSME) on the quality of life in diabetes mellitus patients. The research method used pre-experiment with one group pre test and post test design. The number of samples is 23 people. DSME intervention was given 3 times in Gentungan District Health Center. Gowa. Data were analyzed using the Wilcoxon test with a significant level of 0.05. Wilcoxon results showed a difference in quality of life between the pre test and post test in the treatment group (p = 0.001). Improved quality of life in DM patients after being given DSME intervention. The conclusion is that there is a significant effect of giving DSME on the quality of life of people with DM. DSME can increase the knowledge and self-care abilities of patients in controlling blood sugar and prevent complications that can affect their quality of life.